2019
DOI: 10.48550/arxiv.1910.13773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coexistence of type-I and type-II superconductivity in topological superconductor PdTe$_2$

Abstract: The type-II Dirac semimetal PdTe2 was recently reported to be a type-I superconductor with a superconducting transition temperature Tc 1.65 K. However, the recent results from tunneling and point contact spectroscopy suggested the unusual state of a mixture of type-I and type-II superconductivity. These contradictory results mean that there is no clear picture of the superconducting phase diagram and warrants a detailed investigation of the superconducting phase. We report here the muon spin rotation and relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…These studies have shown the mixed phase of type-I and type-II SC in PdTe 2 [124][125][126]. The critical field (H c ) is observed to vary from 0.0083 to 0.022 T for type-I SC and from 0.025 to 0.32 T for type-II SC [42,86,109,114,118,122,[124][125][126]. Besides, SC in PdTe 2 is quite anistropic [42].…”
Section: Superconductivitymentioning
confidence: 93%
See 4 more Smart Citations
“…These studies have shown the mixed phase of type-I and type-II SC in PdTe 2 [124][125][126]. The critical field (H c ) is observed to vary from 0.0083 to 0.022 T for type-I SC and from 0.025 to 0.32 T for type-II SC [42,86,109,114,118,122,[124][125][126]. Besides, SC in PdTe 2 is quite anistropic [42].…”
Section: Superconductivitymentioning
confidence: 93%
“…Various SC parameters for PdTe 2 are shown in table 2. The T c in PdTe 2 is very sensitive to Te stoichiometry and changes from 1.5 to 1.97 K [86,93,109,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. It is observed that 5% Cu intercalation enhances T c up to maximum value of ∼2.6 K [113].…”
Section: Superconductivitymentioning
confidence: 95%
See 3 more Smart Citations